Resources in Primary Schools: A Challenge for India - Jain, V. K.; Agrawal, Mamta (INDIAN EDUCATIONAL REVIEW, 2011)
Education of children is the primary concern of all countries. In the last two decades, there has been a movement called ’Education for All’ to provide access to all children to school. As a result the enrolment of primary schools which was 78 per cent in the year 1990 increased to 86 per cent in the year 2004 around the world. India was no exception and about 123 million children were enrolled in primary classes according to the 7th All India School Education Survey (7th AISES), 2007, conducted by the National Council of Educational Research and Training (NCERT), New Delhi. This has been possible due to the governmental efforts to provide quality education and in schooling facilities to all children in the age group of 6–14 years